How youth-sport coaches learn to coach - Lemyre, F.; Trudel, P.; Durand-Bush, N. (The Sport Psychologist, 2007)
Researchers have investigated how elite or expert coaches learn to coach, but very few have investigated this process with coaches at the recreational or developmental-performance levels. Thirty-six youth-sport coaches (ice hockey, soccer, and baseball) were each interviewed twice to document their learning situations. Results indicate that (a) formal programs are only one of the many opportunities to learn how to coach; (b) coaches' prior experiences as players, assistant coaches, or instructors provide them with some sport-specific knowledge and allow them to initiate socialization within the subculture of their respective sports; (c) coaches rarely interact with rival coaches; and (d) there are differences in coaches' learning situations between sports. Reflections on who could help coaches get the most out of their learning situations are provided.